Faktor-Faktor yang Mempengaruhi Pertumbuhan di 60 Kabupaten/Kota Sumbagsel Tahun 2017-2021 - Muhari, Muhammad Dheo Adrian; Machfudz, Masyhuri; Suprayitno, Eko (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Southern Sumatra, which consists of the provinces of South Sumatra, Lampung, Jambi, Bengkul, and the Bangka-Beelitung Islands province, has the fastest recovering economic growth compared to other provinces in Indonesia as well as being the highest recovery of economic growth in Sumatra from 2020-2021. By Therefore, this study aims to analyze what factors influence economic growth in 60 cities/regencies in SUMBAGSEL. Keywords: Factors, Economic Growth, SUMBAGSEL